2021
DOI: 10.1002/batt.202100207
|View full text |Cite
|
Sign up to set email alerts
|

Guiding Uniform Sodium Deposition through Host Modification for Sodium Metal Batteries

Abstract: Room‐temperature Na metal batteries represent an emerging energy storage technology beyond Li‐ion batteries, owing to the high specific capacity and high natural abundance of Na. However, Na metal anodes are plagued with multiple challenges including unstable solid electrolyte interphase, undesirable dendrite growth, and large volumetric expansion, leading to low Coulombic efficiency during Na plating and stripping. To this end, mechanically stable and sodiophilic hosts with nano‐ or micro‐structured materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…67,68 Stable interfaces provide uniform deposition of sodium, which mitigates dendritic growth over the anode. 69 The stability of the SEI is related to the chemical nature of electrolytes; the chemical composition of products formed at the interface decides the electrochemical performance and life of a cell. 22,70 It has been reported that Na-S batteries with organic solvent-free solid-state electrolytes, having a wide electrochemical stability window, can effectively prevent diffusion and shuttling of sodium polysulfide to the anode while inhibiting the dendrite growth.…”
Section: Purpose Of Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Stable interfaces provide uniform deposition of sodium, which mitigates dendritic growth over the anode. 69 The stability of the SEI is related to the chemical nature of electrolytes; the chemical composition of products formed at the interface decides the electrochemical performance and life of a cell. 22,70 It has been reported that Na-S batteries with organic solvent-free solid-state electrolytes, having a wide electrochemical stability window, can effectively prevent diffusion and shuttling of sodium polysulfide to the anode while inhibiting the dendrite growth.…”
Section: Purpose Of Reviewmentioning
confidence: 99%
“…67,68 Stable interfaces provide uniform deposition of sodium, which mitigates dendritic growth over the anode. 69 The stability of the SEI is related to the chemical nature of electrolytes; the chemical composition of products formed at the interface decides the electrochemical performance and life of a cell. 22,70…”
Section: Introductionmentioning
confidence: 99%
“…[78,79] In contrast, RT-Na/S delivers a high theoretical specific energy density of 1230 Wh kg À1 with long-term sustainability and safety besides low cost and abundance. [80][81][82][83] The viability of RT-Na/S batteries is severely challenged by the highly corrosive nature of its discharge products, which are identified to be more alkaline than their Li counterparts. [84] In addition to that, the shuttle phenomena are exacerbated in RT-Na/S battery, resulting in higher volumetric fluctuations, i.e., about 170% (in contrast to 70% of volumetric changes in the Li/S system).…”
Section: Rt-na/s Battery Systemmentioning
confidence: 99%
“…[14,15] The hostless nature of the sodium metal anode causes volume change upon stripping/plating, leading to repeated loss of the metal anode and electrolyte inventory. [16] The dendrite growth, which is associated with local current density variation at the surface, is also affected by the hostless nature of the sodium metal anode. Unlike lithium metal dendrites, the sodium dendrites are much weaker, dissociate from the metal surface, and affect the Na metal inventory, causing a sharp decay of the CE.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the sodium metal anode can be stabilized through 3D hosts or current collectors, which can alter the local deposition to control dendrite growth. [16,23] The carbon-based materials have widely been examined as the potential host for the sodium metal anode. [24,25] Many other 3D porous carbon-based materials, for instance, carbon paper with N-doped CNT, [26] carbon fibers, [27] carbon felt, [28] reduced graphene oxides, [29] SnO 2 -CNF, [30] and rGO with MXene, [31] DOI: 10.1002/ente.202200742 An ordered and homogeneous deposition of sodium metal is pivotal in achieving reversible and long-term stability of the metal battery.…”
Section: Introductionmentioning
confidence: 99%